Sustainable development : a model Indonesian SRI co-operative : this research paper is presented in partial fulfilment of the requirements for the degree of Master of International Development, Massey University, New Zealand - Sharp, Gawain (The Author, 2016)
This research report explores how ‘sustainable livelihoods’ have been achieved at a model cooperative using the ‘System of Rice Intensification’ named SIMPATIK. To conduct the research a novel template was developed. The framework was required following a review of sustainable livelihood literature which found deficiencies with the ‘sustainable livelihoods framework’, particularly its treatment of equity, social capital, culture and agro-ecology which disqualified the framework as an appropriate approach for the research. Amekawa’s (2011) ‘Integrated Sustainable Livelihoods Framework’ which synthesises agro-ecology and the sustainable livelihoods framework is then discussed. Further work is then presented on social capital which this paper argues has a critical role in facilitating access to livelihood capitals. A discussion of the significance of culture then follows to underline its importance as a form of livelihood capital. The research then introduces an operational model that is appropriate to the local cultural, institutional and geographical context to demonstrate how livelihood capitals are linked to livelihood outcomes, a model I have labelled the ‘Apt-Integrated Sustainable Livelihoods Framework’. This framework is then informed through field research at the SIMPATIK co-operative. Impact pathways through ‘synergetic forms of social capital’ and the System of Rice Intensification (SRI) are shown indeed to lead to sustainable livelihood outcomes for research participants. The ‘sequencing’ of livelihood capitals is seen to be critical and the research culminates in the development of a ‘SRI Co-operative Template for Sustainable Livelihoods’; a transferable model that shows how SRI can be promoted as a sustainable livelihood strategy.
Keywords: Sustainable development; Agriculture, Cooperative; Rice farming; Economic conditions; Indonesia